2011
DOI: 10.5204/jld.v4i3.79
|View full text |Cite
|
Sign up to set email alerts
|

Developing design and management skills for senior industrial engineering students

Abstract: In Canadian engineering institutions, a significant design experience must occur in the final year of study. In the Department of Industrial and Manufacturing Systems at the University of Windsor, unsolved, open ended projects sponsored by industrial partners from a variety of sectors are provided to the student teams in order for them to apply appropriate design principles to generate original, feasible, working design solutions. Students may be engaged in systems design, facilities layout, optimization or ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…For instance within the field of engineering, Warnock and Mohammadi-Aragh investigated the impact of PBL on student learning in a biomedical materials course and found that students made significant improvements in their problem-solving, communication and teamwork skill 17 . PBL has also been used in senior engineering courses with the same positive results 18,19,20 . Although students in a PBL software engineering course reported that the projects were more time intensive than a typical course project, they were receptive to the approach since they thought it was related to the professional environment and provided them with opportunities to relate theory and practice.…”
Section: Active Learningmentioning
confidence: 99%
“…For instance within the field of engineering, Warnock and Mohammadi-Aragh investigated the impact of PBL on student learning in a biomedical materials course and found that students made significant improvements in their problem-solving, communication and teamwork skill 17 . PBL has also been used in senior engineering courses with the same positive results 18,19,20 . Although students in a PBL software engineering course reported that the projects were more time intensive than a typical course project, they were receptive to the approach since they thought it was related to the professional environment and provided them with opportunities to relate theory and practice.…”
Section: Active Learningmentioning
confidence: 99%
“…PBL has also been used in senior level engineering courses with the same positive results [25], [26], [27]. Although students in a PBL software engineering course reported that the projects were more time intensive than a typical course project, they were receptive to the approach since they thought it was related to the professional environment and provided them with opportunities to relate theory and practice.…”
Section: Active Learningmentioning
confidence: 98%
“…PBL has been used in senior level engineering courses with the same positive results [30], [31], [32]. Although students in one PBL software engineering course reported that the projects were more time intensive than a typical course project, they were receptive to the approach since they thought it was related to the professional environment and provided them with opportunities to relate theory and practice.…”
Section: Active Learningmentioning
confidence: 99%